2001
DOI: 10.1103/physrevlett.86.5550
|View full text |Cite
|
Sign up to set email alerts
|

Bilayer Splitting in the Electronic Structure of Heavily OverdopedBi2Sr2CaCu2

Abstract: The electronic structure of heavily overdoped Bi2Sr2CaCu2O 8+δ is investigated by angle-resolved photoemission spectroscopy. The long-sought bilayer band splitting in this two-plane system is observed in both normal and superconducting states, which qualitatively agrees with the bilayer Hubbard model calculations. The maximum bilayer energy splitting is about 88 meV for the normal state feature, while it is only about 20 meV for the superconducting peak. This anomalous behavior cannot be reconciled with the qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

49
245
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(298 citation statements)
references
References 11 publications
49
245
4
Order By: Relevance
“…This is consistent with the data of Ref. 65. The onset of strong fermionic damping should be independent of the band index, as it is given by scattering to the nodes, and thus occurs at the fixed energy Ω res .…”
Section: G Bilayer Splittingsupporting
confidence: 79%
“…This is consistent with the data of Ref. 65. The onset of strong fermionic damping should be independent of the band index, as it is given by scattering to the nodes, and thus occurs at the fixed energy Ω res .…”
Section: G Bilayer Splittingsupporting
confidence: 79%
“…Eventually, only the BB peak can be seen near (0.2π, π). These features are in good agreement with ARPES experiments [17]. However, the lineshape caused by the phonon-coupling displays a striking contrast to those shown in Fig.3(a) and in experiments [17] , namely, the peak is far below the dip and the dip is below the hump [ Fig.3(b)].…”
Section: Figsupporting
confidence: 72%
“…The RPA correction factor α = 0.34, 0.43 and 0.55 correspond to the critical doping density of the AF instability δ c = 0.02, 0.05 and 0.09, while δ c = 0.02 ∼ 0.05 is within the experimental range [15]. Meanwhile, the ARPES experiment indicated that t ⊥,exp (corresponding to δt p , δ ∼ 0.2) is 44 ± 5meV [17], i.e., t p = 1.6 ∼ 2.0J here. Therefore, in the reasonable parameter range, the interaction between fermions and SF reproduces well the observed antinodal kink.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…As seen from and YBa 2 Cu 3 O 7−x [5]. There might be additional features due to bilayer splitting in the band structure [21,5], and related theoretical results will be presented elsewhere [22]. The theory also predicts a rotation of IAF peak position at very high temperatures which should be verified by future experiments.…”
mentioning
confidence: 74%